2013
DOI: 10.1002/term.1786
|View full text |Cite
|
Sign up to set email alerts
|

Short-term administration of small molecule phenamil induced a protracted osteogenic effect on osteoblast-like MC3T3-E1 cells

Abstract: Sustained administration (21-day treatment) of the small molecule phenamil has been proposed as an alternative osteogenic factor when used in conjunction with a biodegradable scaffold for in vitro osteogenesis. While promising, the major issue associated with small molecules is non-specific cytotoxicity. The aim of this study was to minimize the side-effects from small-molecule drugs by reducing the frequency of administration. Toward this goal, we investigated whether a shorter phenamil treatment is sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…9 Phenamil is a derivative of the FDA-approved diuretic amiloride, an inhibitor of ion transporters. 14,19 A previous study reported that phenamil induced osteoblastic differentiation and mineralization in bone marrow-derived mesenchymal stem cells (MSCs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Phenamil is a derivative of the FDA-approved diuretic amiloride, an inhibitor of ion transporters. 14,19 A previous study reported that phenamil induced osteoblastic differentiation and mineralization in bone marrow-derived mesenchymal stem cells (MSCs).…”
Section: Discussionmentioning
confidence: 99%
“…14,[16][17][18][19] These results suggest that phenamil can work additively or synergistically with BMP-2 to increase bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small molecule phenamil, a derivative of the U.S. Food and Drug Administration-approved diuretic amiloride, is currently attracting attention in bone regeneration due to its osteogenic efficacy through the BMP–Smad signaling pathways [25]. Phenamil induces osteogenic differentiation in mouse bone marrow stromal or preosteoblastic cells and human dental pulp cells [26, 27]. We recently reported the osteogenic activity of phenamil in vitro and bone formation in vivo in a calvarial defect model, both alone and in combination with BMP-2 utilizing a reduced BMP-2 dose [28].…”
Section: Introductionmentioning
confidence: 99%
“…In general, small molecules are small enough to penetrate nontarget cells and trigger unwanted signaling cascades [84]. Thus, the major concern associated with small-molecule therapeutics is their nonspecific adverse effects [10,11,8587]. In addition, a lack of an effective delivery strategy for small molecules is another issue, given that one of the objectives of small molecule-based bone regenerative engineering is to develop an engineered scaffold system that provides adequate doses of the small molecule and/or acts as a structural support for infiltrating cells [11,17,60].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%